Multi-criteria model for classifying clients of companies distributing liquefied petroleum gas - Marcos Felipe Sobral; Ana Paula Cabral Seixas Costa; Adiel Teixeira de Almeida Filho (Brazilian Journal of Operations & Production Management, 2010)
Liquefied Petroleum Gas (LPG) is a fossil fuel that has been attracting a lot of attention in national and global markets because of its logistical versatility, its calorific power, and because it emits a low level of pollutants. The history of its exploitation in the sharply competitive Brazilian market has been marked by various crises which made the exploitation of LPG an activity that has been subject to a number of uncertainties. The product is in the production chain of different market segments and is an important component in the national energy matrix. As a result of this, the process of classifying consumers by LPG distributors is a strategic task and subject to a set of criteria that need to be observed. In this context, this article concentrates on multi-criteria modeling in order to resolve the problematic of classifying clients in a LPG distribution company. A model is proposed based on the ELECTRE TRI method and the aim is to allocate the portfolio of clients to a set of ranked classes.